2019
DOI: 10.3389/fphar.2019.01372
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Implications of Nocebo Effects for Biosimilar Therapy

Abstract: Nocebo effects encompass negative responses to inert interventions in the research setting and negative outcomes with active treatments in the clinical research or practice settings, including new or worsening symptoms and adverse events, stemming from patients' negative expectations and not the pharmacologic action of the treatment itself. Numerous personality, psychosocial, neurobiological, and contextual/environmental factors contribute to the development of nocebo effects, which can impair quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 93 publications
2
68
0
3
Order By: Relevance
“…The way information is conveyed in case of a potential switch can also contribute to a nocebo effect [33]. By avoiding negative associations, one can keep the nocebo effect as small as possible [34]. However, the development of negative associations cannot be fully controlled and can always in uence the outcomes to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The way information is conveyed in case of a potential switch can also contribute to a nocebo effect [33]. By avoiding negative associations, one can keep the nocebo effect as small as possible [34]. However, the development of negative associations cannot be fully controlled and can always in uence the outcomes to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already shown that it is crucial to positively formulate the message about biosimilars towards patients. An empathic and positive communication (including positive framing) or attitude increase the acceptance to switch and reduce the development of nocebo effects after transitioning to a biosimilar [54][55][56][57][58]. An open and positive communication, emphasizing the equalities and not the differences between the reference product and its biosimilar, should be the norm when talking to patients.…”
Section: Communicate Positivelymentioning
confidence: 99%
“…Some patients will naturally be more concerned about their treatment and ask for more information. While other patients trust their physician completely and will express no further concerns about biosimilars [55,60,64]. However, many patients will be somewhere between these two extremes of the spectrum, highlighting the importance of tailored communication.…”
Section: Provide Information Tailored To the Individual Patients' Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have seen a growing increase in the utilisation of biosimilars across countries as a result of ongoing initiatives, and this is likely to continue 39,49-52 enhanced by advice concerning additional initiatives that could be instigated to enhance their use if needed 53 . Education of physicians and patients regarding biosimilars is very important given the nocebo effect in practice else saving goals will not be achieved 54,55 . Such initiatives are likely to grow given the number of biological medicines likely to lose their patent in the near future and the need to enhance the use of biological medicines across countries to improve patient care 56 .…”
mentioning
confidence: 99%